Enhancing Accuracy in Statistics: Examining Work and Performance in Indonesia's BPS - Rangkuti, Samsiah; Yusriani, Sri; Razali, Ali; Nurlinda, Herly; Gunarto, Muji; Azzam, Muhammad Siddiq Idris (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This study delves into the effects of resilience, job resources, and job demands on the performance of BPS's statistical partners mediated by work engagement. The research uses a quantitative method with inferential analysis followed by a cluster sampling method from the questionnaire population of the statistical partner of the Central Statistic Agency (BPS) at the Mandailing Natal district of South Tapanuli in the year 2023. Results show that there is no positive relationship between resilience and performance. Resilience and job resources have a positive and significant effect on work engagement. Job resources and job demand have a positive and significant effect on performance. No positive relationship between resilience and performance. Job demand and work engagement also have no positive relationship. Work engagement mediates the relationship between job resources and performance but does not mediate the relationship between job demand and performance.